Political Parties and Trade Union Growth in Canada - Maki, Dennis (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
This study retests the Ashenfelter-Pencavel hypothesis that political factors matter, using pooled cross section-time series data on union growth for Canadian provinces and a set of dummy variables representing political party in power in each province. Both theoretical and practical aspects are presented.